The Federal Home Loan Bank System: The lender of next-to-last resort? - Adam B. Ashcraft; Morten L. Bech; W. Scott Frame (Federal Reserve Bank of New York, 2008)
The Federal Home Loan Bank (FHLB) System is a large, complex, and understudied government-sponsored liquidity facility that currently has more than 1 trillion in secured loans outstanding, mostly to commercial banks and thrifts. In this paper, we document the significant role played by the FHLB System at the onset of the ongoing financial crises and then provide evidence on the uses of these funds by the System's bank and thrift members. Next, we identify the trade-offs faced by member-borrowers when choosing between accessing the FHLB System or the Federal Reserve's Discount Window during the crisis period. We conclude by describing the fragmented U.S. lender-of-last-resort framework and finding that additional clarity about the respective roles of the various liquidity facilities would be helpful.
Keywords: E40; E59; G21; G28; 330; Federal Home Loan Bank; government-sponsored enterprise; lender of last resort; liquidity; Hypothekenbank; Spezialbank; Lender of Last Resort; Kreditgeschäft; Finanzmarktkrise; USA